Building Home-School Communication Using Technology as a Tool to Enhance Parent Involvement in Primary Schools The case of : SHOUSHA EL- BOUTI primary school -Laghouat - MARFOUA, Imane; MEBARKI ,Khedidja; Nouioua, Amira Hiba (Faculty of Letters and Foreign Languages Department of English, 2017)
Research has documented numerous benefits of parent involvement in children’s education Moreover; their involvement is an important factor for improving academic performance. Thus, Communication between the school and parents constitutes one of the basic types of this engagement, and essential for building trusting relationships that enhance it. Schools attempt to find ways to communicate effectively with parents and some are recently using technology to facilitate this communication. More specifically, Parental involvement in the primary phase is necessary for children to develop successfully. This phase is considered the base of the next educational levels where children need their parents’ support.This study examines how to build home-school partnerships, and how technology such as e-mail and school /classroom websites may be used to bridge the home-school gap in order to enhance parental involvement in today’s primary schools taking SHOUSHA EL-BOUTI primary school as a sample. The research work falls into three chapters. Chapter one includes a theoretical framework about what parental involvement is, its models, procedures and barriers. After that, a full explanation has been given to the area of Technology and its usage. Chapter two is devoted for the description of the methods and procedures used during the research the third chapter seeks to analyze the results to both qualitatively and quantitatively, attempting to answer the questions put forward in the investigation. Data were collected from, an interview with teachers, and questionnaire for parents. Findings of the study showed that although a substantial number of parents do have internet access through home or places of work, yet the use of electronic communication technologies for both parents and teachers is still limited in SHOUSHA EL-BOUTI primary school. Thus, Ministry of education, as well as, schools should be seeking ways to maximize emerging technological tools to promote better communication between teachers and parents.